Bots and automation over Twitter during the third U.S. Presidential Debate - Howard, P; Kollanyi, B; Woolley, S (Political Bots, 2016)
Bots are social media accounts that automate interaction with other users, and political bots have been particularly active on public policy issues, political crises, and elections. We collected data on bot activity using the major hashtags related to the third U.S. Presidential debate. We find that automated pro-Trump accounts became even more aggressive in this final debate, with (1) highly automated pro-Trump accounts launching into content production hours ahead of rather than during the debate and (2) highly automated pro-Trump accounts out producing similar pro-Clinton accounts 7:1 on relevant hashtags. However, we also find that (3) a large number of (human) users still use Twitter for relatively neutral political expression during the debate itself.